Cultura e mudança organizacional: um estudo na Universidade Estadual de Feira de Santana - Bahia - ALMEIDA, Jocely Santos Caldas (2015)
The objective of this paper is to evaluate how the organizational culture from Universidade Estadual de Feira de Santana (UEFS) has influenced the change processes during 2007 until 2013 according to the senior management, teachers, administrative staff and students point of view. We adopted a theoretical vision of culture based in Shein (2009), Hofstede (2003) and Martin Frost (2001) to achieve this goal. We utilised a descriptive, qualitative and quantitative method of research in order to evaluate the process. In the qualitative approach, interviews were conducted with management members and paper analysis. At this stage, the analysis of data collected was based in speech analysis from Fiorin´s (2008) point of view. It associates cultural artifacts to figures while the themes are associated with the organization cultural values. In the quantitative phase we applied surveys to teachers,to business staff and to students with the aim of discovering their opinion about the organizational culture and modernization processes completed. We collected the datum between January and September, 2014. In the first place, the datum indicate that UEFS organization followed the same modernization model followed by most public organizations in Brazil, after management reform. Furthermore, the datum indicate that diferently of the senior management speech and the papers analyzed, the quantitative research has shown that these desired cultural values by top management are not shared by the other organization members, and only the quality and flexibility values to change are perceived by respondents with higher levels of agreement, which also indicates a low share of organizational values within the organization. Finally, the data indicate that there is an important relationship among the cultural values inside UEFS and the understanding of the implemented change processes, indicating that there´s a gap in value sharing which are disseminated by senior management to the other actors. This fact has been affected the change processes to the extent that there is not complete comprehension about these processes.